The vicar of Nibbleswicke - Dahl, Roald; Blake, Quentin (New York Scholastic, 1991)
The vicar's speech impediment leads to holy hysteria in an otherwise quiet country parish.
"First published in Great Britain by Random Century Group, Ltd., 1991"--Half title verso.
Keywords: Clergy -- Fiction; Dyslexia -- Fiction; Speech disorders -- Fiction; Humorous stories